Panorama do IPTU: Um retrato da administraç\~ao tributária em 53 cidades selecionadas - Pedro Humberto Bruno de Carvalho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2018)
– The growing demand for urban infrastructure and public services provided in decentralized way in Brazil, combined with the recent fiscal crisis caused by the economic recession and governmental transfers reduction, has increased the debate about the own municipal taxes strengthening, where the urban property tax would be the first point in the agenda, which causes low economic distortions and can be progressive. Therefore, this study aims to identify the causes of the recent low and heterogeneous level of property tax revenues amongst Brazilian municipalities based on a sample of 53 municipalities (clustered in six groups) to estimate a feasible revenue potential to be achieved, identifying the main barriers of this aim, and proposing legal and administrative reforms. Based on a property tax performance model, the study verified that the sampled property revenues could increase from 0.5% to 0.9% of municipal GDP, which would represent an average increase in total municipal revenues of 12%. This could be reached if the fiscal cadaster coverage increased from 80% to 90%, the taxation on property market values from 0.34% to 0.48%, and the collection rate from 67% to 80%. The study highlights that the main legal and administrative policies to be adopted to reach this potential would include: a) Modernizing and updating the physical and personal database of the fiscal cadasters; b) Implementing technical valuations that reach market values; c) minimizing exemptions and reviewing tax rates level, rather applying selective and progressive tax rates when the intention is to protect the poorer; d) restructuring tax rates in according to budgetary needs and the results of administrative reforms; and e) facilitating voluntary taxpayers' compliance by financial facilities while enforcing delinquency using the "notice of dishonor" of tax arrears under the public notaries. At national level, the proposals of legal reforms would include: a) changing the Fiscal Responsibility Law to include a mandatory 4-years revaluations cycle, and the preparation of administrative municipal tax reports to improve transparency; b) under a comprehensive national tax reform, merging the municipal urban property tax and the federal rural property tax, into a single, locally legislate and administrate broad property tax with fiscal and environmental purposes; and c) expanding and relaxing rules of the national "Program of Modernization of Tax Administrations" (PMAT) to better qualify human resources, incentivizing the creation of intermunicipal corporations that include tax administration purposes, and limiting the program collaterals to the own municipal revenues generated, in order to minimize the budgetary risks and attract more small municipalities.
Keywords: H2; H24; H7; H71; 330; Brazil's property tax; real estate taxation; fiscal federalism; local public finances; tax administration